Factors Affecting Compliance in Paying Land and Building Tax - Fitriani, Fipit; Suhendar, Dadang; Indrawan, Rizki; Putri, Verani Allika (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2026)
This study aims to analyze and produce empirical evidence that can explain the Factors Affecting Compliance in Paying Land and Building Tax in the Kuningan District. The method used in this research is a quantitative, survey-based approach. The sample obtained was 398 respondents. The sampling technique used is Simple Random Sampling. The data analysis technique used is Partial Least Square (PLS) version 4.0. Based on the results of hypothesis testing, it shows that taxpayer understanding has a significant positive effect on compliance in paying land and building tax. Taxpayer awareness has a significant positive effect on compliance in the United Nations. Socialization of Taxation has a significant positive effect on compliance with PBB payments. Tax Sanctions have a significant positive effect on compliance with PBB payments. Economic Factors have no Effect on Compliance in paying PBB. Quality of Service has a significant positive effect on Compliance in PBB.